Single center experience with first-intention high-frequency jet vs. volume-targeted ventilation in extremely preterm neonates - Rallis, Dimitrios; Ben-David, Danielle; Woo, Kendra; Robinson, Jill; Beadles, David; Bernardini, Laura; Abdulhayoglu, Elisa; Flanigan, Elizabeth; Christou, Helen (Frontiers in Pediatrics, 2024)
Objectives To examine whether first-intention high-frequency jet ventilation (HFVJ), compared to volume-targeted ventilation (VTV), in extremely preterm infants is associated with lower incidence of bronchopulmonary dysplasia (BPD) and other adverse clinical outcomes. Study design We conducted a retrospective cohort study evaluating neonates with gestational age (GA) ≤28 weeks, who received first-intention HFJV (main exposure) or VTV (comparator), between 11/2020 and 3/2023, with a subgroup analysis including neonates with GA ≤26 weeks and oxygenation index (OI) >5. Results We identified 117 extremely preterm neonates, 24 (GA 25.2 ± 1.6 weeks) on HFJV, and 93 (GA 26.4 ± 1.5 weeks, p = 0.001) on VTV. The neonates in the HFJV group had higher oxygenation indices on admission, higher inotrope use, and remained intubated for a longer period. Despite these differences, there were no statistically significant differences in rates of BPD, survival, or other adverse outcomes between the two groups. In subgroup analysis of 18 neonates on HFJV and 39 neonates on VTV, no differences were recorded in the GA, and duration of mechanical ventilation, while neonates in the HFJV group had significantly lower rates of BPD (50% compared to 83%, p = 0.034), and no significant differences in other adverse outcomes compared to neonates in the VTV group. In neonates ≤26 weeks of GA with OI >5, HFJV was significantly associated with lower rates of BPD (OR 0.21, 95% CI 0.05–0.92), and combined BPD or death (OR 0.18, 95% CI 0.03–0.85), after adjusting for birth weight, and Arterial-alveolar gradient on admission. Conclusions In extremely preterm neonates ≤26 weeks of GA with OI >5, first-intention HFJV, in comparison to VTV, is associated with lower rates of BPD.